Aktivitas Antibakteri Bacillus yang Berasosiasi dengan Landak Laut di Pantai Mentigi, Lombok Barat - Suryadi, Bambang Fajar; Febrian, Novi (Universitas Atma Jaya Yogyakarta, 2010)
The search for new antimicrobial agents is very significant. The prevalence of antimicrobialresistance among key microbial pathogens is increasing at an alarming rate worldwide. Bacillusspecies produce many kinds of antibiotics which share a full range of antimicrobial activities.The aim of this research is to study antibacterial activity of three bacillus isolates (1A, 2J, 3L)which were isolated in Mentigi Beach, West Lombok. Assessment for antibacterial activity wasconducted using Overlaid Molten agar method on Nutrient Agar medium at different salinity(concentration of NaCl 0, 5, 10%) and different pH (pH 6, 7 and 8). The study showed that therewere different antibacterial activities at different salinity and different pH media. Production ofantibacterial at 0% NaCl concentration occurred only at pH 6 and 7 and had narrow spectrumcharacter (only for Gram positive bacteria). Addition of 5% NaCl made antibacterialproduction might occur at pH 6, 7 and 8 and had wide spectrum character (for Gram positiveand negative bacteria).